2015
DOI: 10.1118/1.4919772
|View full text |Cite
|
Sign up to set email alerts
|

Using multiscale texture and density features for near-term breast cancer risk analysis

Abstract: Purpose: To help improve efficacy of screening mammography by eventually establishing a new optimal personalized screening paradigm, the authors investigated the potential of using the quantitative multiscale texture and density feature analysis of digital mammograms to predict near-term breast cancer risk. Methods: The authors' dataset includes digital mammograms acquired from 340 women. Among them, 141 were positive and 199 were negative/benign cases. The negative digital mammograms acquired from the "prior"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…These techniques were initially developed for use on digitised SFM, but have now been applied to DM and a number of fully automated methods have been developed using a cross-validation approach.Early prospective studies on SFM showed moderate relative risks with texture measures and no additional improvement in discrimination with subsequent addition of MD measures, confirmed in many retrospective studies using increasingly complex texture descriptors and combinations of TA features(173,174). Nielsen et al have developed a mammographic texture resemblance marker (MTR) which demonstrated good discrimination in two completely different cohorts, suggesting the measure is generalisable; the best discrimination was achieved with an aggregate of MTR and Cumulus PMD, with an area under the ROC curve (AUC) of 0.66(175).Studies using DM have attained AUCs of between 0.73(176) to 0.85(177), the latter using a complex combination of texture features. Some TA features may be more predictive of certain tumour subtypes (ER positivity or negativity) (178) and whereas MD does not appear to be predictive of risk in women with…”
mentioning
confidence: 95%
“…These techniques were initially developed for use on digitised SFM, but have now been applied to DM and a number of fully automated methods have been developed using a cross-validation approach.Early prospective studies on SFM showed moderate relative risks with texture measures and no additional improvement in discrimination with subsequent addition of MD measures, confirmed in many retrospective studies using increasingly complex texture descriptors and combinations of TA features(173,174). Nielsen et al have developed a mammographic texture resemblance marker (MTR) which demonstrated good discrimination in two completely different cohorts, suggesting the measure is generalisable; the best discrimination was achieved with an aggregate of MTR and Cumulus PMD, with an area under the ROC curve (AUC) of 0.66(175).Studies using DM have attained AUCs of between 0.73(176) to 0.85(177), the latter using a complex combination of texture features. Some TA features may be more predictive of certain tumour subtypes (ER positivity or negativity) (178) and whereas MD does not appear to be predictive of risk in women with…”
mentioning
confidence: 95%
“…Consequently, more effectively choosing or adaptively optimizing these parameters with different image data sets still needs to be investigated in the future studies. Fifth, although we only extracted the texture features to represent the lung nodule, a number of studies used a large feature set to represent the cancer (e.g., 765 features were computed to represent the breast cancer, 32 and 849 features were computed to represent the lung nodule 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve more reliable and accurate results, several studies including our previous researches have already investigated and tested the possibility of developing computerized schemes to automatically quantify mammographic density and to predict breast cancer risks using computed mammographic image features [9,10]. To the best of our knowledge, all these researches only used single view mammograms, i.e.…”
Section: Introductionmentioning
confidence: 97%